The Profile of Osteogenesis Imperfecta in Dr. Moewardi General Hospital Year 2020-2021: A Retrospective Study - Udi Heru Nefihancoro; Ricat Hinaywan Malik (Jurnal Kedokteran Brawijaya, 2023)
Osteogenesis imperfecta (OI) is a heritable bone dysplasia characterized by bone fragility and long bone deformities. This study aims to report the profile of osteogenesis imperfecta in Dr. Moewardi General Hospital. The patients were searched from the medical record, registered from January 1, 2020, to December 31, 2021, in Dr. Moewardi General Hospital, a tertiary hospital in Surakarta, Indonesia. The data were recorded and described in tables as age, sex, type of OI according to Sillence, clinic, ward admission, signs and symptoms, bisphosphonate therapy and its discipline, as well as the surgical/non-surgical treatment. The quantity of male patients is higher than that of females, OI type IV is the most common, the most common sign/symptoms are fracture and blue sclera, and the most common bone to be fractured is the femur. More than half of patients received bisphosphonate therapy, but only a quarter received it routinely. More than half of patients have performed surgery as the treatment of fractures. Osteogenesis imperfecta patients require an interdisciplinary and tailored treatment that involves both medical and surgical components.